LYRICS & YOU - Nuruljannah Usop (Manes Wordworks, 2024)
Nur Edlynn, a 16-year-old plus-sized girl has been in love with her half-Malay half-British best friend, Tengku Aqeel Zayyan, ever since she was eight. She was confident Aqeel had feelings for her too. She decided to write a love letter, confessing her feelings to Aqeel before he moved to London. However, he decided to cut her off right after Edlynn sent the letter. Edlynn was dejected and disappointed. She was deeply tormented by Aqeel’s ghosting. After five years without contact, Aqeel returns, claiming to rekindle their friendship.